Transformative Power of Constitution of India: A Study in Light of Navtej Singh Johar v. Union of India - Irshad Ahmad; Amit Kashyap (AG Volumes, 2026)
A democratic Constitution like ours is an organic and breathing document, very much alive to its surroundings. It has been created in such a manner that it can adapt to the needs and developments taking place in the society. Therefore, the Constitution of India being a living document also grows and evolves with the changing times. The natural identity of an individual should be treated to be an essential aspect off one’s being. Destruction of an individual’s identity would be tantamount to the crushing of intrinsic dignity that cumulatively encapsulated the value of privacy, choice, freedom of speech and other expressions. Therefore, the case of Navtej Singh Johar v. Union of India is a watershed moment in development of India’s legal history, marking a significant milestone in the recognition and protection of individual rights and equality, decriminalizing the colonial criminal penal provision. This chapter aims to examine the transformative power of the Constitution of India, in the light of particularly the case of Navtej Singh Johar. The authors have analysed its impact on societal norms, protection of the individual rights and legal precedents. This chapter explores how the judgment of the Apex Court has contributed to social transformation, evolution of legal principle and the protection of fundamental rights in India.